Characterization of peripheral cytokine-secreting cells responses in HIV/TB co-infection - Tan, Yuting; Guo, Wei; Zhu, Qi; Song, Shihui; Xiang, Yanni; Wu, Songjie; Zou, Shi; Yan, Yajun; Feng, Ling; Luo, Mingqi; Shen, Ling; Feng, Yong; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Currently the responses of peripheral cytokine-secreting cells in the natural course of human immunodeficiency virus (HIV) and tuberculosis (TB) co-infection haven’t been fully elucidated. Methods The function of peripheral proinflammatory, regulatory and cytotoxic cytokine-secreting cells were investigated by direct intracellular cytokine staining (ICS) and flow cytometry, additionally, the absolute numbers of different cytokine-secreting cells were measured among patients with HIV/TB co-infection (HT group), and compared them with the healthy controls (HC group), patients with TB (TB group) and patients with HIV infection (HIV group). After one week’s anti-TB treatment, the changes of the percentages of cytokine-secreting cells were further evaluated in TB and HT groups. Results Totally 26 individuals in the HC group, 51 in the TB group, 26 in the HIV group and 29 in the HT group were enrolled. The HT. HT group exhibited significantly lower absolute numbers of IFN-γ+CD4+, IFN-γ+CD8+, TNF-α+CD4+, IL17A+CD4+ T cells and TNF-α+CD14+ monocytes than the TB and HIV groups. Compared with the TB group, the percentages of CD8+ T cells secreting IFN-γ and perforin (p=0.010; p=0.043) were significantly lower among the HT group. Compared with the HIV group, the percentages of CD4+, CD8+ T cells and CD14+ monocytes secreting TNF-α (p=0.013; p=0.001; p<0.001) were significantly decreased, and the percentage of CD8+ T cells secreting IL-17A (p=0.015) was significantly increased among the HT group. Both the percentages of CD4+ T cells secreting TGF-β (p<0.001; p=0.001), and CD4+ and CD8+ T cells secreting granzyme A (all p<0.001), were significantly higher among the HT group than among the TB group and HIV group. After one week’s anti-TB treatment, an increased percentage of CD4+ T cells secreting TNF-α (p=0.003) was found in the TB group, and an increased percentage of CD8+ T cells secreting TNF-α (p=0.029) was found in the HT group. Conclusion Significantly different functional profiles of peripheral proinflammatory, regulatory, and cytotoxic cytokine-secreting cells were observed in the natural course of HIV/TB co-infection compared to TB and HIV infection alone, even though the absolute numbers of those cells were significantly lower in HIV/TB co-infection. TNF-α-secreting CD8+ T cells may be a more sensitive marker for early evaluation of anti-TB treatment efficacy in patients with HIV/TB co-infection.